A P300 Brain-Computer Interface With a Reduced Visual Field - Kirasirova, Luiza; Bulanov, Vladimir; Ossadtchi, Alexei; Kolsanov, Alexander; Pyatin, Vasily; Lebedev, Mikhail (Frontiers in Neuroscience, 2020)
A P300 brain-computer interface (BCI), also called BCI speller, is a paradigm, where text characters are decoded from event-related potentials (ERPs). Although many strategies have been proposed for improving the BCI spelling, a relatively simple one received insufficient attention: reduction of the visual field to diminish the contribution from non-target stimuli. Previously, this idea was implemented in a single-stimulus switch that issued an urgent command. To tackle this approach further, we ran a pilot experiment where subjects operated a traditional P300 speller or wore a binocular aperture that confined their sight to the central visual field. Visual field restriction resulted in a replacement of non-target ERPs with EEG rhythms asynchronous to stimulus periodicity. Changes in target ERPs were found in half of the subjects and were individually variable. While classification accuracy was slightly better for the aperture condition (84.3 ± 2.9%, mean ± standard error) than the no-aperture condition (81.0 ± 2.6%), this difference was not statistically significant for the entire sample of subjects (N=10). Classification accuracy improved over four days of training, more so for the aperture condition (from 72.0 ± 6.3% to 87.0 ± 3.9% and from 72.0 ± 5.6% to 97.0 ± 2.2% for the no-aperture and aperture conditions, respectively). We suggest that with further refinement this approach could speed up BCI operations and reduce user fatigue. We further discuss how a P300 speller could be improved by taking advantage of the different physiological properties of the central and peripheral vision.